Fluid Osmolarity Acutely and Differentially Modulates Lymphatic Vessels Intrinsic Contractions and Lymph Flow - Solari, Eleonora; Marcozzi, Cristiana; Negrini, Daniela; Moriondo, Andrea (Frontiers in Physiology, 2018)
Lymph formation and propulsion rely on an extrinsic mechanism based on the forces that surrounding tissues exert upon the vessel wall and lumen and an intrinsic mechanism based on spontaneous, rhythmic contractions of the lymphatic muscle layer of collecting vessels. The two spontaneous pacemakers described in literature involve chloride-dependent depolarizations (STDs) and If-like currents, both giving rise to a variable contraction frequency (fc) of lymphatic vessels functional units (lymphangions). Several stimuli have been shown to modulate fc, such as temperature, shear stress, and several tissue chemical modulators (prostaglandins, norepinephrine, acetylcholine, substance P, and others). However, no detailed description is present in literature on the acute modulation of fc by means of osmolarity change of the surrounding interstitial space. Using a well-developed ex-vivo rat diaphragmatic preparation, in which osmolarity was changed by varying the concentration of D-mannitol in the perfusing solution and in later experiments the concentration of NaCl and then of Na+ and Cl- ions separately by ionic substitution, we provide detailed experimental evidences that a stepwise increase in osmolarity from control value (308 mOsm) up to 324 mOsm caused a reduction of fc down to ~-70% within the first 14 minutes, and that a stepwise decrease in osmolarity up to 290 mOsm induced an early fc increase to ~+34% of control, followed by a decline to an fc of ~-18% of control value. These variations were more dramatic when the same osmolarity changes were obtained by varying NaCl and/or Na+ or Cl- ions concentration, which caused an almost complete arrest of spontaneous contractility within 14 minutes from the application. Diastolic and systolic diameters and stroke volume were not affected by osmolarity changes, so that modulation of lymph flow closely followed that of fc. Modulation of lymph flow secondary to osmolarity changes is relevant if one considers that interstitial fluid balance is also dependent upon lymph drainage, and thus it is possible that, at least in the acute phase following variations of interstitial fluid osmolarity, its volume control might eventually be impaired due to the reduced or in the worst scenario null lymph drainage.